Development and Validation of a UHPLC–MS/MS Method for Quantitation of Almonertinib in Rat Plasma: Application to an in vivo Interaction Study Between Paxlovid and Almonertinib - Tang, Peng-fei; Bao, Su-su; Gao, Nan-yong; Shao, Chuan-feng; Xie, Wei-fei; Wu, Xue-meng; Zhao, Le-ping; Xiao, Zhong-xiang (Frontiers in Pharmacology, 2022)
Almonertinib was approved for the first-line treatment of advanced NSCLC patients with EGFR-TKI-sensitive genetic mutations by National Medical Products Administration (NMPA) in 2021. The purpose of this study was to establish and validate a fast, accurate, stable and facile ultra-performance liquid chromatography-tandem mass spectrometry method for the quantification of almonertinib in rat plasma, it was employed to explore the drug interactions of almonertinib with Paxlovid in rats. Zanubrutinib was used as an internal standard (IS), and the plasma samples were prepared by the protein precipitation method using acetonitrile. Chromatographic separation was carried out on a Shimadzu LC-20AT ultra-performance liquid chromatography system using a Shim-pack velox C18 (2.1× 50 mm, 2.7 μm) column. The mobile phase consisted of methanol and 0.1% formic acid-water. Mass spectrum analysis was executed using Shimadzu 8040 Triple quadrupole mass spectrometry. The precursor and product ions of the analyte and internal standard were detected in multiple reaction monitoring (MRM) mode. The typical fragment ions were m/z 526.20 → 72.10 for almonertinib and m/z 472.15 → 290.00 for zanubrutinib (IS). The method was validated to have good linearity for quantifying almonertinib in rat plasma from 0.1-1000 ng/ml (R2=0.999), and the LLOQ was 0.1 ng/ml. The validity of this method was sufficiently verified for selectivity, specificity, extraction recovery, matrix effect, accuracy, precision and stability. The validated UHPLC–MS/MS method was successfully applied to the drug interaction study of almonertinib with Paxlovid in rats. Paxlovid significantly inhibits the metabolism of almonertinib and increased the exposure of almonertinib. This study can help us to understand the metabolic profile of almonertinib better, and further human trials should be conducted to validate the results.